The Socio-Cultural Role of the Batak Community in the Development of Lake Toba Tourism - Yulia Sitepu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to explore and analyze the social and cultural role of the Batak community in building and developing Lake Toba tourism in Samosir Regency. As a beautiful island inhabited by the Toba Batak ethnicity, Lake Toba not only has beautiful natural scenery, but also has culture and local wisdom that can attract tourists to learn about it. This research is qualitative research that describes the socio-cultural descriptive of the Toba Batak people. Data was collected through observation, interviews, as well as document searches and previous research results. The analysis was done descriptively. The results of the study are that social and cultural have a very important role in the process of developing Lake Toba tourism. We can see the interaction of the Toba Batak Tribe based on the social motives that make people successful, namely the achievement motive, the motive for power and the motive for friendship. In the daily life of the Batak people, they provide services for local and foreign tourists. Toba Batak culture which has life guide values such as hagabeon, hamoraon and hasangapan can be used as a daily habit in providing tourism services to tourists. The role of the local government also has a very important role to provide direction and socialization for the local community or tourism business actors to promote the cultural values of the Toba Batak to tourists so that tourists are interested in coming back to Parapat City to display good and interesting cultural tourism attractions.